UW-RF dining services meal plan participant survey report - Hadley, Shelly; Trechter, David; Janke, James; Parks, Denise; Gunter, Ramona (My University, 2007)
The motivation for this study was to evaluate preferences and gather opinions of meal plan participants at the University of Wisconsin-River Falls (UW-RF). Dining Services at UW-RF wanted to understand how to best meet the needs of meal plan participants as they prepare a contract for a new food service provider.
75 p.
Keywords: University of Wisconsin-River Falls. Dining Services; University of Wisconsin-River Falls food services; University of Wisconsin-River Falls meal plan; University of Wisconsin--River Falls--Students--Nutrition; College students--Wisconsin--River Falls--Nutrition; Food habits; Universities and colleges--Food service--Wisconsin--River Falls